Peach cobbler murder - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2005)
When Shawna Lee Quinn, a rival bakery owner, is found shot to death in the back of the Magnolia Blossom Bakery, Hannah Swenson becomes the prime suspect in the crime and, with a little help from her friends, sets out to serve up the real killer.